Structural, electromagnetic and microwave properties of magnetite extracted from mill scales via conventional ball milling and mechanical alloying techniques - Elmahaishi, Madiha Fathi; Azis, Raba’ah Syahidah; Ismail, Ismayadi; Mustaffa, Muhammad Syazwan; Abbas, Zulkifly; Matori, Khamirul Amin; Muhammad, Farah Diana; Saat, Nor Kamilah; Nazlan, Rodziah; Ibrahim, Idza Riati; Abdullah, Nor Hapishah; Mokhtar, Nurhidayaty (MDPI AG, 2021)
This study presents the utilization of mill scale waste, which has attracted much attention due to its high content of magnetite (Fe3O4). This work focuses on the extraction of Fe3O4 from mill scale waste via magnetic separation, and ball milling was used to fabricate a microwave absorber. The extracted magnetic powder was ground-milled using two different techniques: (i) a conventional milling technique (CM) and (ii) mechanical alloying (MM) process. The Fe3O4/CM samples were prepared by a conventional milling process using steel pot ball milling, while the Fe3O4/MM samples were prepared using a high-energy ball milling (HEBM) method. The effect of milling time on the structural, phase composition, and electromagnetic properties were examined using X-ray diffraction (XRD) and a vector network analyzer (VNA). XRD confirmed the formation of magnetite after both the magnetic separation and milling processes. The results revealed that Fe3O4 exhibited excellent microwave absorption properties because of the synergistic characteristics of its dielectric and magnetic loss. The results showed that the Fe3O4/CM particle powder had a greater absorption power (reflection loss: <−10 dB) with 99.9% absorption, a minimum reflection loss of −30.83 dB, and an effective bandwidth of 2.30 GHz for 2 mm thick samples. The results revealed the Fe3O4/MM powders had higher absorption properties, including a higher RL of −20.59 dB and a broader bandwidth of 2.43 GHz at a matching thickness of only 1 mm. The higher microwave absorption performance was attributed to the better impedance matching property caused by the porous microstructure. Furthermore, the magnetite, Fe3O4 showed superior microwave absorption characteristics because of the lower value of permittivity, which resulted in better impedance matching. This study presents a low-cost approach method by reutilizing mill scale waste to fabricate a high purity crystalline Fe3O4 with the best potential for designing magnetic nano-sized based microwave absorbers.